Seleksi Mutan Generasi Dua (M2) Kedelai Hitam Terhadap Produksi Tinggi - Siti Novridha Andini; Jaenudin Kartahadimaja; Miranda Ferwita Sari (Politeknik Negeri Lampung., 2021)
The number of black soybean varieties in Indonesia is less than the yellow one. Black soybeans contain anthocyanin which is good for health. Black soybean is also the raw material of soy sauce and other food processing. The genetic diversity of black soybean varieties needs to be increased to improve the genetic using plant breeding. The mutation is a method of plant breeding to produce a new variety. This research aims to get the high production genotypes and the observational variables that are used for M3 selection. This research used a non-factorial randomized block design. The treatments were 0 Gy, 50 Gy, 100 Gy, 150 Gy, 200 Gy that repeated three times, so was obtain 15 experimental units, with each experimental unit contains 6 rows and consist of 4 plants. The seven observation variables that consist of plant height; the number of branches, flowering age, number of pods, harvesting age, the weight of 100 grains, and the weight of seeds per plant were analyzed for the diversity using NTSYS software, and the coefficient of genotype diversity was calculated. The genotypes that had high production at the 50 Gy dose were 1 (11), 4 (25), 6 (25), and 2 (26); for the 100 Gy dose were 1 (14), 6 (25), 1 (11), 4 (1); for the 150 Gy dose were 3 (19), 5 (10), and 6 (1); and for the dose 200 Gy were 1 (19) and 1 (26), and the observational variables that are selected for M3 selection were the number of branches, number of pods, and seed weight per plant.